2020
DOI: 10.1186/s43046-020-00029-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological significance of immunohistochemically marked tumor-associated macrophage in classic Hodgkin lymphoma

Abstract: Background: Tumor-associated macrophages (TAM) are pivotal in remodeling of the tumor immune microenvironment and clinical outcome. Herein, we aim to evaluate the impact of immunohistochemical (IHC) expression of CD68 and CD163 in TAM on clinico-pathological features, patients' response to therapy and the overall survival (OS). Results: This retrospective study was performed on paraffin-embedded tissue blocks of 100 classic Hodgkin Lymphoma (cHL) cases diagnosed and treated at our Institution. Immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This finding implies that elevated levels of soluble receptor CD163 may be a common feature among patients with DLBCL. In recent years, several studies have demonstrated the roles of TAMs and CD163 in the pathogenesis of hematopoietic malignancies including T-cell leukemia/lymphoma, acute myeloid leukemia, and classical Hodgkin lymphoma [ 17 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In most studies, high CD163 expression was correlated with an inferior prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that elevated levels of soluble receptor CD163 may be a common feature among patients with DLBCL. In recent years, several studies have demonstrated the roles of TAMs and CD163 in the pathogenesis of hematopoietic malignancies including T-cell leukemia/lymphoma, acute myeloid leukemia, and classical Hodgkin lymphoma [ 17 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In most studies, high CD163 expression was correlated with an inferior prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The lower level of M2 macrophages has been linked to a complete response and better survival [305]. The expressions of both TAM markers, CD68, and CD163 [306] are essential predictors of complete remission in CHL patients [307]. A high ratio of LAMs to Hodgkin-Reed-Sternberg cells at diagnosis is associated with a higher risk of CHL progression or death [308].…”
Section: Hodgkin Lymphomamentioning
confidence: 99%